Collagen Type I as a Ligand for Receptor-Mediated Signaling - Boraschi-Diaz, Iris; Wang, Jennifer; Mort, John S.; Komarova, Svetlana V. (Frontiers in Physics, 2017)
Collagens form the fibrous component of the extracellular matrix in all multi-cellular animals. Collagen type I is the most abundant collagen present in skin, tendons, vasculature, as well as the organic portion of the calcified tissue of bone and teeth. This review focuses on numerous receptors for which collagen acts as a ligand, including integrins, discoidin domain receptors DDR1 and 2, OSCAR, GPVI, G6b-B and Lair-1 of the leukocyte receptor complex and mannose family receptor uPARAP/Endo 180. We explore the process of collagen production and self-assembly, as well as its degradation by collagenases and gelatinases in order to predict potential temporal and spatial sites of action of different collagen receptors. While the interactions of the mature collagen matrix with integrins and DDR are well-appreciated, potential signals from immature matrix as well as collagen degradation products are possible but not yet described. The role of multiple collagen receptors in physiological processes and their contribution to pathophysiology of diseases affecting collagen homeostasis require further studies.